Effects of chlorination and ultraviolet light on environmental tetracycline-resistant bacteria and tet(W) in water. Issue 1 (February 2017) - Sullivan, Bailey A.; Vance, Cherish C.; Gentry, Terry J.; Karthikeyan, Raghupathy
Abstract: The effectiveness of traditional water disinfection methods against both environmental antibiotic resistant bacteria (ARB) and antibiotic resistant genes (ARGs) is still not well understood. The study objective was to evaluate two common methods for reducing concentrations of not only culturable tetracycline-resistant bacteria but also a resistance tet (W) gene fragment that has been frequently detected in the environment. Disinfection experiments were performed by exposing tetracycline-resistant isolates to various dosages of sodium hypochlorite or ultraviolet irradiation (UV). Concentrations of resistant bacteria and the tet (W) gene fragment were determined at 0 and 24 h after disinfection using traditional plating techniques and qPCR, respectively. Both the UV and chlorine disinfection methods were highly effective in initially reducing bacterial concentrations, and the chlorine disinfection method was more effective in preventing regrowth. However, both UV and chlorine disinfection were less consistent at reducing the concentration of the tet (W) gene fragment than for culturable resistant-bacteria at the dosages studied. Results indicated that after disinfection, resistance genes may remain detectable even if culturable resistant-bacteria are not, and that environmental ARBs and ARGs may survive these commonly used methods.